ANALISIS KESALAHAN MORFOLOGI PADA KARANGAN MAHASISWA TINGKAT II TAHUN AJARAN 2015/2016 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU - Yayuk Ade Kartika; Zuli Laili Isnaini; Sri Wahyu Widiati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research describes the error in morphology which is done by second student of Japanese Language Education Department University Of Riau. This research uses quantitative and qualitative description methode. Error analysis by Heidi Dulay (1981) is the theory which is used in this research. The theory consists 5 kinds of error,that are omission, addition, missformation, alternating form, and misordering. The error data is got from 28 of students result of essays in sakubun II class which topic are「楽しい一日」 and 「日本でびっくりっしたこと」. According to data analysis result, there are 4 errors: omission as many as 27 errors, addition as many as 8 errors, missformation as many as 54 errors and alternating from as many as 1 errors. In conclusion, the error which appears at most is missformation error, while alternating form error is the least. From interview result and connection in all of sakubun, there are mistake and error classification. There are 96 mistakes in mistake, while 70 mistakes in error.Keywords : Error Analysis, Sakubun, Morphology.